ASUHAN KEBIDANAN IBU BERSALIN DENGAN ATONIA UTERI PADA NY. “H” DI BPM BD. HJ. OOM ROCHMULYATI, S.ST TAHUN 2019 - Qonita; Nadya Rahmah (Journal Of Applied Health Research And Development, 2019)
According to the Indonesia Demographic Health Survey (SDKI) (2015), said that the Maternal Mortality Rate (MMR) in Indonesia reached 305 per 100,000 live births. Based on data from the Health and Information Center of the Ministry of Health (2015) the causes of maternal death are bleeding (30.3%), hypertension (28.8%), and pregnant women with anemia (37.1%). One cause of maternal death is bleeding. The cause of bleeding that needs serious attention is Atonia Uteri, because if the handling is late it will worsen the situation and can threaten the life of the mother. The incidence of uterine atony is around 1-3% of all deliveries. The purpose of this case study is to be able to carry out maternity care with Atonia Uteri in Ny. "H" at BPM Bd. Hj. Oom Rochmulyati, S.ST 2019 with midwifery service standards. The method used in this case study is a qualitative case study. After the assessment, the results obtained from objective and subjective data show that Ny. H has Atonia Uteri. Then given care to Mrs. H, i.e. put an IV drip infusion with 20 IU 40 TPM and do KBE (Extra Biamnual Compression) for 30 minutes while monitoring the mother's bleeding and vital signs. The evaluation was achieved bleeding resolved and good contractions. It is expected that all health services can improve the quality of comprehensive care services for maternity women more accurately, especially for mothers with atony uteri